Manajemen Pembelajaran Anak Usia Dini Berbasis Saintifik di Ra Ar Rafif Kalasan Sleman - Sumartin, Sumartin (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2017)
The purpose of this research is to knowthescientific-based learning process applied in Raudhatul Athfal (RA).In more detail, the purpose of this research are to describe the management of scientific-based learning process in RA, describes the advantages and disadvantages of scientific-based learning process in RA and describe the impact of scientific-based learning process in RA. Methodology of this reseacrh was qualitative descriptive. The technique of data collecting are through observation, interview, and documentation. The technique of data analysis was through data reduction, data presentation,  verified and  deduced. The validation tests were research triangulation, method, theory and data source. The results show that: (1) the implementation of scientific-based learning process include: activities to observe, ask, explore (collecting information), associates, and communicate (2) the advantages and disadvantages scientific-based learning process can be seen from the pre learning, learning process and learning evaluation activities (3) the impact of this scientific-based learning process can be perceived by the various parties include teachers, students and the general society.